Discovering the Meaning of Figurative Language in Jamie Miller’s Song Lyrics - Desak Putu Eka Pratiwi; Ida Ayu Putri Gita Ardiantari; Bagul, Apolinarius (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The purpose of this study is to identify the types of figurative language and the meaning intended. Two theories have been used in this study. The first theory is presented by Kennedy (1987) as used to identify the types of figures of speech used in Jamie miller's song lyrics. A second theory is presented by Leech (1974) to learn the meaning of the figures of speech used in Jamie Miller's song. The method used in data collection is the method of observation. The writers collect data of song lyrics by browsing and downloading song lyrics from the Internet, reading, listening, and understanding song lyrics, taking note and classifying data based on the types of figurative language. The writer analysed the data in a descriptive way using a qualitative method. After analyzing the data, the writer found that there are six types of figurative of language used in Jamie Miller's song lyrics which consist of 2 metaphors (16,6%), 2 similes (16,6%), 2 personifications (16,6%), 1 paradox (8,3%), 2 apostrophe (16,6%), and 3 hyperbole (24,9%). All of figurative language have a connotation that implicitly conveys hidden messages and values of life.